Amnesty : a novel - Adiga, Aravind (Scribner, 2020)
Danny- formerly Dhananjaya Rajaratnam- is an illegal immigrant in Sydney, Australia, denied refugee status after he fled from Sri Lanka. Working as a cleaner, living out of a grocery storeroom, for three years he<U+2019>s been trying to create a new identity for himself. And now, with his beloved vegan girlfriend, Sonja, with his hidden accent and highlights in his hair, he is as close as he has ever come to living a normal life. But then one morning, Danny learns a female client of his has been murdered. The deed was done with a knife, at a creek he<U+2019>d been to with her before; and a jacket was left at the scene, which he believes belongs to another of his clients- a doctor with whom Danny knows the woman was having an affair. Suddenly Danny is confronted with a choice: Come forward with his knowledge about the crime and risk being deported? Or say nothing, and let justice go undone? Over the course of this day, evaluating the weight of his past, his dreams for the future, and the unpredictable, often absurd reality of living invisibly and undocumented, he must wrestle with his conscience and decide if a person without rights still has responsibilities.